Features of haemophilus influenzae type b vaccine in patients waitlisted for lung transplantation - V. B. Polishchuk; M. P. Kostinov; A. A. Pyzhov; O. O. Magarshak; N. E. Yastrebova; N. A. Karchevskaya; E. A. Тarabrin; T. E. Kallagov; A. E. Vlasenko (Вестник трансплантологии и искусственных органов)
Objective: to evaluate the immunological efficacy of haemophilus influenzae type b (Hib) vaccine in patients with severe bronchopulmonary condition waitlisted for lung transplantation. Materials and methods. 16 patients (age 22–61 years) with severe bronchopulmonary diseases were vaccinated once against Hib infection. IgG antibody concentrations to Hib capsular polysaccharide before vaccination and 1 month after was measured by ELISA using a test system developed at Mechnikov Research Institute of Vaccines and Sera. Statistical data processing was carried out using stats (v.3.6.2), lme4 (v.1.1 – 21), and lmerTest (v.3.1 – 1) packages. Results. Hib vaccine in patients with severe bronchopulmonary condition did not elicit any local or systemic reactions. The proportion of patients whose antibody (Ab) concentrations to Hib capsular polysaccharide exceeded the long-term protection threshold was 69% and 100% before and after vaccination, respectively (p = 0.02). There were differences in the formation of post-vaccination immunity depending on the nosological forms of patients’ diseases. In the group of patients with obstructive pulmonary diseases, the geometric mean level of antibodies to the Hib capsular polysaccharide after vaccination increased as compared to the baseline  value – from 1.3 [0.6–2.8] to 5.5 [1.9–15.4] AU/mL, (p = 0.05). In the group of patients with restrictive lung diseases, the level did not change – 2.8 [0.6–14.1] AU/mL before vaccination and 3.4 [1.3–8.5] AU/mL 1 month after vaccination. In the group of patients taking glucocorticosteroids, there was no increase in the level of antibodies to Hib capsular polysaccharide (2.7 [0.8–9.3] AU/mL before and 2.8 [1.2–6.5] AU/mL after vaccination). In the group of patients who did not take hormones, antibody concentrations to Hib capsular polysaccharide increased from 1.2 [0.7–2.1] AU/mL to 4.8 [2.2–10.1] AU/mL (p = 0.006). Conclusion. Hib vaccination of waitlisted patients with severe bronchopulmonary disease is safe and immunologically effective.